The Difference of Bovine Bone Graft and Iliac Crest Bone Graft Effect on Closure of Bone Defect in Alveolar Bone Graft in Dr. Moewardi Hospital and Panti Waluyo Hospitals, Surakarta - Bahtiar, Ruzbih; Kurniasih, Dewi Haryanti; Alifianto, Untung (Indonesian Journal of Medicine, 2018)
Background: Cleft lip and palate (CLP) is a case of craniofacial congenital abnormalities that are often found by plastic surgeons. Successful management requires good surgical techniques, deep understanding of anatomical abnormalities and three-dimensional aspects of facial aesthetics. The Alveolar bone graft (ABG) aims to unite and stabilize Maxilla before definitive orthodontic action and restoration of dental care. The use of bone grafts in the surgical field is often done, aimed at maximizing the process of bone healing. Autogenous bone graft is the gold standard bone graft material because it contains all the properties needed in bone formation. The iliac crest bone graft (ICBG) is the most commonly used donor. Bromine bone graft (BBG) is increasingly being used as a substitute for autogenous bone graft. The purpose of this study was to determine the differences in the effect of the percentage of defect closure between CNG and ICBG on the closure of defects in ABG.Subjects and Method: The retrospective cohort study was conducted at Dr. Moewardi and Panti Waluyo Hospitals, Surakarta, Central Java, Indonesia, from February to April 2018. The dependent variable was bone defect closure. The independent variables were bovine bone and iliac crest bone grafts. The data were analyzed by Mann-Whitney.Results: Most patients after ABG surgery have a percentage of bone defect closure of 75-100% with bone resorption of 0-25% and include type I Bergland scale, where ICBG (66.7%) tends to be better than BBG (55.6%), but statistically not significant (p value = 0.678).Conclusion: There is no difference in the effect of the percentage of defect closure between CNG and ICBG on the closure of defects in ABG. ICBG tends to give a better percentage of defect closure than CNG, but it is not statistically significant.Keywords: Cleft lip and palate (CLP), Alveolar bone graft, bovine bone graft, Iliac crest bone graft, closure of bone defects.Correspondence: Ruzbih Bahtiar. Department of Surgery, Dr. Moewardi Hospital, Surakarta/Faculty of Medicine, Universitas Sebelas Maret.  Indonesian Journal of Medicine (2018), 3(3): 151-161https://doi.org/10.26911/theijmed.2018.03.03.05